2017
DOI: 10.1039/c6qo00655h
|View full text |Cite
|
Sign up to set email alerts
|

Transition-metal-free direct perfluoroalkylation of quinoline amides at C5 position through radical cross-coupling under mild conditions

Abstract: A simple low-energy and efficient method is established for the synthesis of C5-selective perfluoroalkylation quinolines in the absence of any transition metal catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 87 publications
0
20
0
Order By: Relevance
“…To the best of our knowledge, transition‐metal‐free direct C−H trifluoromethylation of nonprefunctionalized heterocyles using TMSCF 3 as trifluoromethyl agent near room temperature is less reported ,. In addition, compared to trifluoromethylation, efficient and general methods for direct C−H perfluoroalkylation of nonprefunctionalized heterocyles with TMSC 2 F 5 or TMSC 3 F 7 are comparatively rare ,,,. Thus, expanding the application of TMSC n F 2n+1 (n=1, 2, 3) in the fluorination of organic compound with higher atom‐efficient as well as getting the useful fluoroalkylated molecules is still challenging.…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, transition‐metal‐free direct C−H trifluoromethylation of nonprefunctionalized heterocyles using TMSCF 3 as trifluoromethyl agent near room temperature is less reported ,. In addition, compared to trifluoromethylation, efficient and general methods for direct C−H perfluoroalkylation of nonprefunctionalized heterocyles with TMSC 2 F 5 or TMSC 3 F 7 are comparatively rare ,,,. Thus, expanding the application of TMSC n F 2n+1 (n=1, 2, 3) in the fluorination of organic compound with higher atom‐efficient as well as getting the useful fluoroalkylated molecules is still challenging.…”
Section: Methodsmentioning
confidence: 99%
“…In 2017, Zhang's research group demonstrated PIDA-mediated C-H perfluoroalkylation of 8-aminoquinoline amides 369 to yield perfluoroalkylated quinolones 371 (Scheme 100). 130 Reaction scope was administered by using different perfluoroalkyl sources 370 such as TMSC2F5, TMSn-C3F7 and TMSCF3. Based on the various control experiments, it was confirmed that reaction proceeds via single electron transfer mechanism.…”
Section: Alkylation/alkynylation Of Heterocylesmentioning
confidence: 99%
“…In 2017, Zhang and co‐workers reported a simple and effective method for the preparation of 5‐perfluoroalkylquinoline amides involving the C‐5 selective perfluoroalkylation of quinoline amides via coupling of 8‐aminoquinoline amides with perfluoroalkyl compounds (Scheme ) . The reaction is characterized by transition metal‐free catalysis, mild conditions (room temperature), short reaction times and high yields, and tolerance of various functional groups.…”
Section: Para‐c–h Functionalization Of Aromatic Amidesmentioning
confidence: 99%